Terrestrial Mobile Robot Undercarriagedisambiguation With Stress On Mecanum Wheels - Davídek, Daniel (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
The first step in new mobile robot design is the selection of undercarriage. If you are designing terrestrial robot you have commonly two options how to create movement with your actuators: a legged or wheeled drive. To select on of these categories, you should now the nature of the surface the mobile robot will most often get across. In this article commonly used wheeled drives and a few of legged robot examples are described with special attention to the omnidirectional Mecanum wheel undercarriage.
Keywords: terrestrial mobile robot; differential drive; ackerman drive; omniwheels; mecanum wheels